State changes in posture and arch of the foot in children aged 4 - 6 years with hypermobility of the joints under the influence of rehabilitation activities in schools - Kalinichenko I. O.; Dyachenko Y. L. (Kharkov National Pedagogical University, 2013)
The effect of the rehabilitation activities in educational institutions on the dynamics of changes in the state and posture of the foot arch in children. The study involved 446 children aged from 4 to 6 years. The rehabilitation program lasted 10 weeks and consisted of 3 periods. Found that 35.88% of healthy children had impaired posture in the sagittal plane. Flatfoot detected in 64.46% of children with joint hypermobility. After the implementation of the rehabilitation program the value of the brachial arch indicators declined in children 3 major groups, respectively, 32.85 cm, 33.24 cm and 33.92 cm in all major groups established downward trend in the proportion of children with kyphotic posture and flat feet. The positive dynamics of changes in the values of posture in the sagittal plane was observed among children of all 3 major groups: shoulder width increased respectively by 1.55%, 3.09%, 4.77%.